Genetic Analysis of a Horizontal Resistance Locus BLMR2 in Brassica napus - Zhang, Qiang; Dandena, Hanna; McCausland, Madison; Liu, Huizhi; Liu, Zheng; Xu, Wen; Li, Genyi (Frontiers in Plant Science, 2021)
Previous studies have shown that BLMR2 was located on chromosome N10 and conferred horizontal resistance under field conditions. The spectrum of resistance to Leptosphaeria maculans isolates of the resistance locus BLMR2 was analyzed using near isogenic lines, resistant, and susceptible cultivars. The results showed that this locus was horizontally resistant to all isolates tested. Sequence characterized amplified polymorphism (SCAR), simple sequence repeats (SSR) and single nucleotide polymorphism (SNP) markers were developed in the chromosome region of BLMR2 and a fine genetic map was constructed. Two molecular markers narrowed BLMR2 in a 53.37 kb region where 6 genes were annotated. Among the six annotated genes, one encoding a cytochrome P450 protein was predicted as the candidate of BLMR2. Based on the profiling of pathogen induced transcriptome, three expressed genes in the six annotated genes were identified while only cytochrome P450 showed upregulation. The candidate corresponds to the gene involved in the indole glucosinolate biosynthesis pathway and plant basal defense in Arabidopsis thaliana. The molecular markers identified in this study will allow the quick incorporation of the BLMR2 allele in rapeseed cultivars to enhance blackleg resistance.